Meningkatkan Kemampuan Menulis Teks Puisi melalui Pendekatan Konstruktivisme - Nurul Sulasmiyatningsih (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The ability to write poetry is an important skill for students to develop creativity, imagination and critical thinking abilities. However, based on observations at the research location, it shows that students' ability to write poetry is still low. This can be seen from the results of poetry that is less creative and imaginative. This research aims to improve students' ability to write poetry texts through the application of a constructivist approach. This approach emphasizes the activeness and involvement of students in building their knowledge through experience and interaction with their environment. The subjects of this research were 11 students in class X SMA Sawerigading Makassar. The instruments used by researchers were test sheets and observation sheets. Then the data analysis technique uses descriptive statistical analysis to obtain average information and percentage of learning completeness. The results of the study in the first cycle of students who completed were only 3 or 27.27% and this increased to 11 students or 100% who completed in cycle II. In cycle I the average score of students was only 67.27, increasing to 80.90 in cycle II. The highest score in cycle I was only 80, increasing to 90 in cycle II and the lowest score in cycle I was 55, increasing to 75 in cycle II. Based on these results, it can be stated that the constructivist approach can be an effective learning alternative to improve students' ability to write poetry texts.